Changes in pulmonary function and their correlation with dose–volume parameters in patients undergoing stereotactic body radiotherapy for lung cancer. (22nd January 2021) - Takemoto, Shinya; Shibamoto, Yuta; Hashizume, Chisa; Miyakawa, Akifumi; Murai, Taro; Yanagi, Takeshi; Sugie, Chikao; Nagai, Aiko
Abstract: It is desirable to estimate the degree of the decrease in pulmonary function before lung stereotactic body radiation therapy (SBRT) especially for patients with poor pulmonary function. The purpose of this study was to investigate whether decreases in pulmonary function after SBRT may be predicted from radiation dose–volume parameters. A total of 70 patients undergoing SBRT were evaluated for changes in pulmonary function. Of these, 67 had primary lung cancer and 3 had lung metastasis. Twenty-six (37%) patients had chronic obstructive pulmonary disease. Pulmonary function tests (PFTs) were performed shortly before and at 18–24 months after SBRT. Radiation pneumonitis was Grade 2 in 10 patients and Grade 3 in 1. Mean forced vital capacity (FVC) decreased from 2.67 to 2.51 L ( P  < 0.01) and mean forced expiratory volume in 1 s (FEV1) decreased from 1.80 to 1.72 L ( P  < 0.01). Planning target volume (PTV) was correlated with changes in FVC. Changes in percent predicted FVC were correlated with %V5Gy (% of lung volume receiving > 5 Gy) and %V40Gy . Although the correlation was not significant, the %V20Gy value was the closest to the percent reduction in predicted FVC; %V20Gy of 10% tended to be associated with ~10% reduction in predicted FVC. Patients with poor pulmonary function did not necessarily show greater decreases in each PFT parameter. Decreases in FVC and FEV1 were within previously reported ranges. PTV was associated with decreases in FVC. The %V20Gy value was closest to the percentage decrease in predicted FVC.